Autocatalytic polymerization of selenium/polypyrrole nanocomposites as functional theranostic agents for multi-spectral photoacoustic imaging and photothermal therapy of tumor. (September 2020) - Zhang, J.; Qiu, T.; Lan, Y.; Tu, C.; Shang, T.; Lin, Y.; Mao, G.; Yang, B.
Abstract: The synchronization of diagnosis and treatment is a new trend in cancer treatment. Photoacoustic imaging (PAI) and photothermal therapy (PTT) are recognized as one of the perfect combinations. The autocatalytic polymerization of selenium/polypyrrole (Se@PPy) nanocomposites with a wide-absorption band at near-infrared region (NIR, 800 nm) has been developed in this paper. The wide optical absorption characteristics enable Se@PPy nanocomposites to achieve multi-spectral PAI. Ex vivo experiments show desirable photoacoustic ability of the Se@PPy nanocomposites at wavelengths ranging from 700 nm to 900 nm, which is better than that of commercial indocyanine green (ICG). Se@PPy nanocomposites have high photothermal conversion efficiency up to 36.3% as well as excellent photo-thermal stability. In vitro cytotoxicity test demonstrates that the Se@PPy nanocomposites have good bio-safety. Furthermore, the feasibility of Se@PPy nanocomposites for enhancing multi-spectral PAI guided PTT was verified on 4T1 tumor-bearing nude mice. Our results indicate that Se@PPy nanocomposites could be used as an effective theranostic agent for near-infrared light-mediated PAI and PTT of tumor. Graphical abstract: Autocatalytic polymerization of Se@PPy nanocomposites with excellent biocompatibility for PAI-guided PTT for the treatment of breast cancer. Image 1 Highlights: The autocatalytic polymerization of Se@PPy nanocomposites with absorption band at near-infrared region has been developed. Se@PPy nanocomposites have good bio-safety, desirable photoacoustic ability and high photothermal conversion efficiency. Se@PPy nanocomposites could be used for photoacoustic imaging and photothermal therapy of tumor.